Development of ADR mechanisms in Kenya and the role of ADR in labour relations and dispute resolution - Nyakundi, Freda Moraa (Institute of Development and Labour Law, 2015)
Alternative Dispute Resolution (ADR) is a vastly growing enterprise in conflict management the world over. Its application in managing labour relations and the attendant disputes has been tested and is well settled. Kenya, in recognition of this phenomenon, has adopted a legal framework making provisions for both ADR and Labour rights in its most supreme law, the Constitution of Kenya, 2010. This informs the theme of the current study. The disciplines that are ADR and labour relations are overwhelmingly extensive. Thus they cannot find conclusive commentary in a single book leave alone a thesis with a predicated word count. This paper is neither a one stop-shop treatise nor an integral text on either disciplines but a comprehensive commentary, on the interplay between ADR and labour relations. Fair treatment has been accorded and care has been borne to neither starve one nor belabor the other. It is a commentary spanning eons, reaching out to the past, tracking development and addressing the prevailing circumstances in respect of ADR's application in labour dispute resolution in Kenya. The rich literature review (books, statutes, conventions, journals, articles) quoted is as informative as it is illuminating, and presents a wealth of knowledge. The overall aim is to assess the place of ADR in labour relations in Kenya and spur academic, intellectual and sector-wise debate on the foregoing.